Prosocial behavior as a protective factor against gambling addiction problems in university students - Esparza-Reig, Javier (2020)
This research seeks to analyze the variables involved in prosocial behavior and his ability to act as a protective factor against gambling addiction. This study is quantitative, descriptive, cross-sectional and correlational. The sample was made up of 258 adults residing in the province of Valencia (59.5% women) with a mean age of 20.95 years (SD = 2.19). Questionnaires were applied to measure the variables involved (Brief Resilient Coping Scale, cuestionario de apoyo social, Escala de Prosocialidad y South Oaks Gambling Screen) and a structural equation model was performed. The results showed good fit indices (X2 (41) = 59.31, p = .06; CFI = .97; GFI = .96; RMSEA = .04) and indicated that social support and resilience were not related, being both predictors of prosocial behaviors. Furthermore, prosocial behaviors were predictors of gambling addiction. This research presents an explanatory model of prosocial behaviors (30%) and gambling addiction problems (8%), which, if replicated, can be very useful at clinical and university fields, helping to understand the functioning of prosocial behaviors and incorporating this knowledge for the development of programs that promote social values.